Mosquito-Borne Diseases Related Knowledge and Perception among Residents of Semi Urban Region of Eastern Nepal - Acharya, Alok; Yadav, Amar Kumar; Upadhyay, Priya; Kumar, Surendra (Journal of Nobel Medical College, 2017)
Background : Mosquito borne diseases are endemic in most part of the country. While public health efforts are placed towards the elimination of major vector borne diseases like malaria and filariasis, climatic and manmade environmental changes has led to threats of reemergence of mosquito borne diseases like dengue and chikungunya in new regions. There are needs of studies among community people regarding knowledge and perception of vector borne diseases to change the attitudes of people towards vector control and avoid risky behavior by application of behavior change communication tools.Material & Methods: A cross sectional study was done among households from 2 wards of Tankisinwari VDC in semi-urban region near Biratnagar sub-metropolitan city. The study duration was of 3 months from November 27 2014 to February 27 2015. Study population was 566 and 654 households from 2 wards. Among them, 57 from one ward and 65 from other ward, a total of 122 households were taken proportionately from both wards. Data was entered into excel sheet and analysis was done using SPSS 16.Results: People who heard of filariasis as disease transmitted by mosquito bite were 23.8% and malaria (89.3%), Dengue (19.6%). Among the participants, 85% responded that mosquito borne disease can be prevented in their area while 4.9% and 6.6% only heard of indoor residual spraying and insecticide treated bed nets respectively. Among those who did not know about breeding places of mosquito, 29.2% were illiterates, who were significantly more than literates 5.1% (p